Effectiveness of 4th doses of bivalent mRNA vaccine in reinfections from October 2022 to October 2023 in a general medicine office in Toledo (Spain) - Turabian, Jose Luis (Archives of Community Medicine and Public Health, 2024)
Background: The effectiveness of the COVID-19 vaccine in preventing reinfections is uncertain and there is little community-level research published at this time. Objective: To compare the cases of COVID-19 reinfections in vaccinated versus not vaccinated 4th dose people with bivalent mRNA vaccines and assess the effectiveness of this vaccine booster. Methodology: An observational, longitudinal, and prospective case series study of adult patients with COVID-19 reinfections in general medicine from October 1, 2022, to October 1, 2023. The 4th dose vaccine COVID-19 effectiveness was calculated as 1 - [COVID-19 cases incidence of reinfection with 4th dose vaccine / COVID-19 cases incidence of reinfection without 4th vaccine dose] × 100. Results: 12 COVID-19 reinfections were included. Of them, 5 were in people with a fourth vaccine dose of bivalent mRNA and 7 were in people without a fourth vaccine dose of bivalent mRNA. The population vaccinated with the 4th dose was estimated at 1,133 people. The population without a 4th dose was estimated at 867 people. The 4th dose of bivalent mRNA vaccine effectiveness to prevent reinfections calculated on the total number of cases of reinfections in vaccinated and unvaccinated was 30%. The 4th dose of bivalent mRNA vaccine effectiveness to prevent reinfections calculated on population denominators of the total number of people vaccinated or not, was 46%. Conclusion: In the context of general medicine in Toledo (Spain), the 4th dose of bivalent mRNA vaccine effectiveness to prevent reinfections was modest. However, these results should be interpreted with caution because of the few cases included and possible underreporting.